2010
DOI: 10.1002/lapl.201010039
|View full text |Cite
|
Sign up to set email alerts
|

Supercontinuum generation up to 2.5 μm in photonic crystal fiber made of lead-bismuth-galate glass

Abstract: In this paper we report on successful supercontinuum generation extending from the near to the mid-infrared region in the range 700-2500 nm in a micro-structured fiber made of lead-bismuth-galate glass and pumped in the femtosecond regime with a wavelength of 1540 nm. The flatness of 5 dB is observed in most of the registered spectrum 1000 -2500 nm. The improved spectral and thermo-physical properties of this custom made lead-bismuth-galate glass against tellurite and commercially available heavy oxide SF-57 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 30 publications
1
64
0
Order By: Relevance
“…Miret et al [9] have reported 3 dB flat SC spectra spanning over ~1500 nm by using femtosecond pulse in a 15 cm PCF which exhibits normal dispersion. Buczynski et al [11] have also reported about 1500 nm wide SC spectra in lead-bismuth-galate glass PCF by pumping femtosecond pulses at operating wavelength 1540 nm.Tiwari et al [8] generated SC spectra from 1000 nm to 3200 nm by using 50 fs pump pulse of peak power 2 kW in a 15 cm long PCF. Along this direction, we focus our attention to achieve broadband SC generation at low input power.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Miret et al [9] have reported 3 dB flat SC spectra spanning over ~1500 nm by using femtosecond pulse in a 15 cm PCF which exhibits normal dispersion. Buczynski et al [11] have also reported about 1500 nm wide SC spectra in lead-bismuth-galate glass PCF by pumping femtosecond pulses at operating wavelength 1540 nm.Tiwari et al [8] generated SC spectra from 1000 nm to 3200 nm by using 50 fs pump pulse of peak power 2 kW in a 15 cm long PCF. Along this direction, we focus our attention to achieve broadband SC generation at low input power.…”
Section: Introductionmentioning
confidence: 95%
“…For example, PCFs made of fluoride glass, bismuth oxide, lead silicate, tellurite and chalcogenide etc., exhibit large effective nonlinearity which is suitable for devices that rely on optical nonlinearity. Particular interest has been shown to lead silicate glass with nonlinear coefficient which is 20 times larger than that of silica glass and has good thermal and crystallization stability [11,12]. Lead silicate glass fibers exhibit attenuation ~1-3 dB/m at the operating wavelength 1.55…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metal oxide glasses such as SF6 and SF57 offer a large Raman shift and high nonlinearity [5,6]. Highly nonlinear PCFs made of such glasses have been used successfully for broadband supercontinuum ge− neration with a low intensity input pulses [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in many earlier works that slicing of a broadband continuum spectra is capable of generating a multiwavelength laser comb with both spacing tunability and a very wide spectral range (Nan et al, 2004). The supercontinuum light can be produced from a pulsed laser by using the interaction of multiple nonlinear effects such as self-phase modulation (SPM), four-wave mixing (FWM) and stimulated Raman scattering (SRS) in a highly nonlinear optical fiber (Buczynski et al, 2009(Buczynski et al, , 2010Kurkov et al, 2011;Lehtonen et al, 2003;Chen et al, 2011;Gu et al, 2010;Akozbek et al, 2006). Spectral slicing allows the channel spacing to be adjusted by changing the length of polarization maintaining fiber (PMF) used in the loop mirror (Ahmad et al, 2009).…”
Section: Introductionmentioning
confidence: 99%